Temperature dependent otolith growth of larval and early juvenile Atlantic cod (Gadus morhua) - Otterlei, E.; Folkvord, A.; Nyhammer, G. (ICES Journal of Marine Science, 2002)
The otolith (lapillus) size–fish size relationship was examined for offspring of two Atlantic cod stocks, reared at different temperatures. Larvae and early juveniles reared at high temperatures (fast growing), had larger otoliths at a given length than fish reared at low temperatures (slow growing). Within a given temperature group, however, faster growing cod tended to have proportionally smaller otoliths, although the difference was not always significant. Moreover, the otolith radius of Norwegian coastal cod was larger, at given fish lengths, compared to that of the northeast Arctic cod. An ontogenetic shift in the allometric otolith size–fish size relationship occurred at onset of metamorphosis (12 mm). Mean daily otolith growth of the lapillus radius increased with increasing temperature from 4 to 14°C and was size dependent and peaked at a larval length of about 25 mm. The radius of the lapillus at hatching was poorly correlated with larval length at day 56 for both stocks, suggesting that the potential for fast growth may not necessarily be reflected in traits present at hatching. The effects of temperature, stock and ontogeny are discussed with regard to the assumption of constant proportionality between otolith growth and fish growth.